Inequitable inefficiency: A case study of rail transit fare policies - Zakhary Mallett (Journal of Transport and Land Use)
Transit fare equity research overwhelmingly measures equity based on disparity in the fare paid for travel without consideration of the costs of service delivery. Research also ignores the cost-sharing nature of transit—as more riders consume it, the average cost per rider declines. Together, this leaves an incomplete understanding about who receives more subsidy. This study measures equity by analyzing spatial and temporal cost recovery variability of two rail systems, BART in the San Francisco Bay Area and MARTA in Atlanta. I scale origin-destination trip cost recoveries to stations and operating time periods and find that travel associated with outlying areas and off-peak times receive more subsidy. I further find that subsidy patterns are marginally progressive; they positively correlate with select disadvantaged socioeconomic groups. I offer ideas on why these findings appear divergent from past research.